Measuring Nature of Science Views of Middle School Students - İREZ, OSMAN SERHAT (IJATE-INT JOURNAL ASSESSMENT TOOLS EDUCATION, 2019)
Developing scientific literacy for all students is the most often stated purpose of contemporary science education. Nature of science (NOS) is seen as an important component of scientific literacy. There are various perceptions of NOS in the science education community and NOS itself is an ever-changing construct. This makes it challenging to develop instruments for measuring understanding of NOS at different levels. Many instruments have been developed and are being developed to assess NOS learning, which indicates the importance attributed to this subject. In this study, we developed a multiple-choice test to measure NOS understanding of middle school students. The instrument was applied to 1397 middle school students. The 24 item multiple-choice test had KR-20 reliability coefficient of 0.74. A 12 item multiple-choice test created as a subset of the 24 items of the original test. This test was easier and had higher discrimination, which can provide useful measurement data about students' understanding of NOS for diagnostic or formative purposes.
Keywords: Nature of science; Middle school; Assessment; Multiple choice; CONCEPTIONS; INSTRUMENT